2008
DOI: 10.5271/sjweh.1193
|View full text |Cite
|
Sign up to set email alerts
|

Driver impairment at night and its relation to physiological sleepiness

Abstract: Anund A, Kecklund G, Peters B, Forsman Å, Lowden A, Åkerstedt T. Driver impairment at night and its relation to physiological sleepiness. Scand J Work Environ Health. 2008;34(2):142-150.Objectives Studies of devices detecting sleepiness need reference points of physiological sleepiness. The present study sought to validate the Karolinska drowsiness score (KDS) as an indicator of physiological sleepiness against driving impairment and eye blink duration during a 45-minute drive in an advanced moving-base drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…It responded very clearly to sleep loss, as well as to time on task. The pattern is very similar to that of other studies using the same scale (KSS) [8][9][10] , but again, the peak levels in the present study was about one unit lower than the usually encountered level 9.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It responded very clearly to sleep loss, as well as to time on task. The pattern is very similar to that of other studies using the same scale (KSS) [8][9][10] , but again, the peak levels in the present study was about one unit lower than the usually encountered level 9.…”
Section: Discussionsupporting
confidence: 78%
“…This is rather remarkable, considering all the studies that show severe effects of sleep loss on eye blinks 10,11,14) . There doesn't seem to exist any comparable data but in a study of effects of time of day on the risk of different types of crashes it was found that the only type of crash without a late-night peak in relative accident risk was that due to overtaking 20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of driver sleepiness normally involves indicators such as the standard deviation of the lateral position (O'Hanlon and Kelly, 1974;Otmani et al, 2005), frequent subjective ratings of sleepiness during driving (Åkerstedt et al, 2005;Anund et al, 2008b;Ingre et al, 2006a) the electroencephalogram (EEG) with its content on alpha band (8-12 Hz) and theta band (4-8 Hz) activity (Horne and Reyner, 1996;Gillberg et al, 1996) as well as the electrooculogram (EOG). The latter may involve increased duration of eye blinks (Dinges et al, 2005) or slow rolling eye movements (Åkerstedt and Gillberg, 1990).…”
Section: Introductionmentioning
confidence: 99%